ROLE OF HEMOTRANSFUSION IN THE BURN SURGERY - L. P. Loginov (Неотложная медицинская помощь, 2016)
ABSTRACT. The article covers the history of over a 60-year experience of dermatome skin grafting in burn patients. The study emphasizes a great contribution of Academician B.A. Petrov in the development of dermatome skin grafting methodology, its principles remaining unchanged so far. Based on his own observations, the author states that anemia complicating the severe burn course and the lack of anemia prevention caused by a number of factors make a negative impact on the outcome in operative burn treatment, leading to a gradual loss of dermatome skin grafting principles. The author makes a conclusion on the necessity of adequate blood transfusions in patients with severe burns in order to keep the red blood parameters normal.